1990
DOI: 10.1021/bi00462a021
|View full text |Cite
|
Sign up to set email alerts
|

Rearrangement of the distal pocket accompanying E7 His .fwdarw. Gln substitution in elephant carbonmonoxy- and oxymyoglobin: proton NMR identification of a new aromatic residue in the heme pocket

Abstract: Two-dimensional 1H NMR methods have been used to assign side-chain resonances for the residues in the distal heme pocket of elephant carbonmonoxymyoglobin (MbCO) and oxymyoglobin (MbO2). It is shown that, while the other residues in the heme pocket are minimally perturbed, the Phe CD4 residue in elephant MbCO and MbO2 resonates considerably upfield compared to the corresponding residue in sperm whale MbCO. The new NOE connectivities to Val E11 and heme-induced ring current calculations indicate that Phe CD4 ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…Thus, for El-Mb the linear coupling constants for the 370 and 1357 cm-1 modes are considerably smaller than those observed in Sw-Mb and Ho-Mb, whereas for the 674 cm-' mode Si is larger. Considering that the Soret band arises from a n --r* electronic transition within the heme ring and that the heme is planar in CO derivatives while being domed in the deoxy derivatives, we suggest that this feature arises from differences in heme doming between El-Mb and Sw or Ho-Mb; plausibly, this is related to the crowding of the El-Mb heme pocket observed by NMR spectroscopy (Yu et al, 1990;Vyas et al, 1993) and described in the introduction. Moreover, the reduced intensity of the peaks in the 300-400 cm-1 region of the RR spectra of El-Mb compared with Sw-Mb (Kerr et al, 1985) agreeswith the smaller S370value obtained in this work.…”
Section: Resultsmentioning
confidence: 70%
See 2 more Smart Citations
“…Thus, for El-Mb the linear coupling constants for the 370 and 1357 cm-1 modes are considerably smaller than those observed in Sw-Mb and Ho-Mb, whereas for the 674 cm-' mode Si is larger. Considering that the Soret band arises from a n --r* electronic transition within the heme ring and that the heme is planar in CO derivatives while being domed in the deoxy derivatives, we suggest that this feature arises from differences in heme doming between El-Mb and Sw or Ho-Mb; plausibly, this is related to the crowding of the El-Mb heme pocket observed by NMR spectroscopy (Yu et al, 1990;Vyas et al, 1993) and described in the introduction. Moreover, the reduced intensity of the peaks in the 300-400 cm-1 region of the RR spectra of El-Mb compared with Sw-Mb (Kerr et al, 1985) agreeswith the smaller S370value obtained in this work.…”
Section: Resultsmentioning
confidence: 70%
“…Compared to Sw-Mb, El-Mb is characterized by a markedly reduced autooxidation rate (Romero-Herrera et al, 1981), an increased redox potential (Bartnicki et al, 1983), and a decreased CO dissociation rate, the association constant being practically unchanged (Romero-Herrera et al, 1981). The structure at the distal side of the heme pocket of El-Mb has been investigated by two-dimensional NMR spectroscopy (Yu et al, 1990;Vyas et al, 1993) and by resonance Raman (RR) spectroscopy (Kerr et al, 1985). The former investigation indicates the presence of a phenylalanine in the heme pocket of El-Mb located where a cavity is found in Sw-Mb and interacting with the bound ligand; this leads to a crevice that is both more crowded and hydrophobic than in Sw-Mb.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As naturally occurring distal residues, histidine and glutamine are more common in invertebrate hemoglobins and myoglobins. These residues are capable of forming a hydrogen bond with the bound dioxygene and of stabilizing it (Phillips and Schoenborn, 1981;Nagai et al, 1987;Yu et al, 1990). Moreover the site-directed mutagenesis studies of the distal(E7) residue in sperm whale myoglobin showed that the substitution by Gly, Val, Phe, Cys, Met, Lys, Arg, Thr, and Asp increased the rate of autoxidation 40-to 350-fold, in which Asp was the largest (350-fold) (Springer et al, 1989).…”
Section: Resultsmentioning
confidence: 99%
“…A more crowded distal pocket for P. epiclitum Mb than other Mbs, Hbs is supported by the observed line broadening of the Phe 46 (CD1) ring protons. In spite of its close proximity to the heme, 1 H NMR has shown that this highly conserved aromatic ring undergoes rapid 180°ring reorientation that completely averages the environments of the two H ⑀ (and two H ␦ ) ring protons in common Mbs and Hbs (27,33,34). The significant broadening of the Phe 46 (CD1) H ⑀ resonance (Fig.…”
Section: Discussionmentioning
confidence: 99%